Serum antiretinal antibodies and cytokine profiling in autoimmune retinopathy and their association with clinical outcomes - Zeng, Hui-Yang; Liu, Qian; Cao, Kai; Wang, Ning-li; Wang, Yujia; Zhang, Zi-jun; Ge, Qing (Graefe's archive for clinical and experimental ophthalmology, 2023)
Purpose Autoimmune retinopathy (AIR) is a group of autoimmune retinal diseases that can cause blindness. The purpose of this study is to investigate the profiles of serum antiretinal antibodies (ARAs) and cytokines and their association with disease diagnosis as well as clinical features in AIR. Methods The patients with presumed para (p) and non-paraneoplastic (np) AIR diagnosis, the patients with retinitis pigmentosa and bilateral uveitis as disease controls, and healthy subjects were prospectively enrolled. Western blotting and Luminex multiple cytokine assay/enzyme linked immunosorbent assay were used to determine the presence of serum ARAs and the concentration of cytokines, respectively. Kruskal–Wallis or chi square test was applied to compare the profiles of ARA and cytokines among various groups. The multilevel mixed-effect regression was used to investigate the association of ARA or cytokines with clinical features. Results No significant difference in the band number and subtypes of serum ARAs was found between AIR patients and their controls. AIR patients had higher concentration of serum IFN-ɤ, CXCL9, or CXCL10 than non-AIR controls. A positive correlation was found between increased number of ARAs and elevated TNF-α in np-AIR patients. Elevated pro-inflammatory cytokines or ARA subtypes (antibody against recoverin and α-enolase) were associated with worse retinal functions or anatomy, including visual acuity, visual field, ERG parameters, and central retinal thickness. Conclusions The data of our study demonstrate that detection of serum ARAs has limited value in the diagnosis of AIR. Th1-type cytokines/chemokines or specific ARA subtypes are associated with pathogenesis and disease severity of the AIR.